There's a lid for every pot! The relationship between performance measurement and administrative activities in Italian ministries - Giovanni Barbato; Alessandro Salvadori; Matteo Turri (Cogent Business & Management, 2018)
Following the spread of performance measurement (PM) in public organisations, a vast literature has developed on its functioning and difficulties. This paper intends to investigate the relationship between administration activities, which can by their nature have different characteristics, and PM systems. The application of PM in the Italian ministries through the analysis of 1,511 objectives/indicators shows the relevance of administrative activities in influencing the ability to measure performance and suggests that neglecting this link is detrimental to the evaluation system and undermines its ability to provide a reliable representation of the contribution of public organisation in relation to performance.
Keywords: 650